Challenges for flood risk management in flood‐prone Sirajganj region of Bangladesh. Issue 1 (22nd May 2018) - Ali, Md.H.; Bhattacharya, B.; Islam, A.K.M.S.; Islam, G.M.T.; Hossain, Md.S.; Khan, A.S.
Abstract : Although Bangladesh has suffered from different types of floods which have caused enormous damage to properties and lives, managing floods still remains a challenging task. Flood management is a multisectoral activity due to its complexity, scale, and multidisciplinary nature. Sirajganj district can be regarded as one of the most vulnerable areas in Bangladesh and hence a study was carried out for Sirajganj district to provide guidelines to combat challenges to flood risk management. The flood frequency analyses at three river stations using water level data were carried out, the flood inundation map for different return periods and a flood depth versus damage curve are plotted to address the vulnerable areas and damages, and to help design flood mitigation structures. It can be inferred that damages will be proportional to return period since the risk is a function of hazard, vulnerability, and exposure. Both structural and non‐structural measures including rejuvenation of the Jamuna River and low‐cost flood resistant building approaches for flood affected char (island) people are suggested along with a few recommendations to mitigate floods in the study area. The government, Non governmental organization (NGO), funding agencies, and transboundary countries should come forward to mitigate flood hazards to improve the livelihood of the affected people.